The Jewish question and Verwoerd: editorship of the die Transvaler 1937-1948 - Du Toit, Karen S. (My University, 2019)
The 1930s and 40s marked a tumultuous political period in South Africa. Central political players and their respective parties, whether government, opposition, extra-parliamentary or other all jostled for power. Socio-economic and political events locally and on a global scale merged with religionationalistic ideology to mobilise Afrikaners into a collective and to form a maelstrom within which antisemitism flared up in the country. This rise of antisemitism created a serious ‘Jewish Question’ in South Africa and is the entry point for this research paper which takes a closer look at the reasons for the content of the opinion piece that Verwoerd, as editor of this Nationalist Party paper, penned in the first edition of Die Transvaler in October 1937, namely the ‘Nationalist viewpoint on the Jewish Question: the solution’ which effectively championed economic antisemitism. It also looks more in depth at the media libel case between Verwoerd and The Star and finds that there were multiple instances of falsification of news in the court case that found Verwoerd guilty of promoting Nazi propaganda and making his paper a tool for the Nazis during the Second World War. The outcome of this research directly links Dr. H.F. Verwoerd’s negative portrayal of the Jewish Question in Die Transvaler with the intent to mobilise Afrikaner Nationalism in the lead up to the 1948 elections.
A research report submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Masters of Arts in Journalism and Media Studies March 2019
Keywords: Afrikaners; South Africa--Politics and government--1909-1948